Studi Kelayakan Bisnis Berdasarkan Aspek Teknis dan Operasional pada Mie Gacoan (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This discusses the business feasibility study of Mie Gacoan based on technical and operational aspects. Mie Gacoan, as one of the main players in the Indonesian culinary industry, faces the challenge of fierce competition. By offering innovations in products and services, as well as effective marketing strategies, Mie Gacoan has managed to attract the attention of customers. This study uses a qualitative approach to analyze various aspects, including planning, production control, and product design. The results of the study show that menu innovation and good customer service are the keys to Mie Gacoan's success in achieving sustainable growth.